The Respiratory Microbiome in Cystic Fibrosis: Compartment Patterns and Clinical Relationships in Early Stage Disease - Garcia-Nuñez, Marian; Garcia-Gonzalez, Miguel; Pomares, Xavier; Montón, Concepción; Millares, Laura; Quero, Sara; Prina, Elena; Asensio, Oscar; Bosque, Montserrat; Capilla, Silvia; Cuevas, Oscar; Monsó, Eduard (Frontiers in Microbiology, 2020)
We compared the bacterial microbiomes lodged in the bronchial tree, oropharynx and nose of patients with early stage cystic fibrosis (CF) not using chronic antibiotics, determining their relationships with lung function and exacerbation frequency. CF patients were enrolled in a cohort study during stability and were checked regularly over the following 9 months. Upper respiratory samples (sputum [S], oropharyngeal swab [OP] and nasal washing [N]) were collected at the first visit and every three months. 16S rRNA gene amplification and sequencing was performed and analysed with QIIME. Seventeen CF patients were enrolled (16.6 SD 9.6 years). Alpha-diversity of bacterial communities between samples was significantly higher in S than in OP (Shannon index median 4.6 [IQR: 4.1-4.9] vs. 3.7 [IQR: 3-1-4.1], p=0.003 / Chao 1 richness estimator median 97.75 [IQR: 85.1-110.9] vs. 43.9 [IQR: 31.7-59.9], p=0.003) and beta-diversity analysis also showed significant differences in the microbial composition of both respiratory compartments (Adonis test of Bray Curtis dissimilarity matrix, p=0.001). Dominant taxa were found at baseline in 5 patients (29.4%), who showed lower forced expiratory volume in the first second (FEV1%, mean 74.8 [SD 19] vs. 97.2 [SD 17.8], p=0.035, Student t test). The Staphylococcus genus had low RAs in most samples (median 0.26% [IQR 0.01%-0.69%]), but patients with RA>0.26% of Staphylococcus in bronchial secretions suffered more exacerbations during follow-up (median 2 [IQR 1-2.25] vs. 0 [0-1], p=0.026. Mann-Whitney U test), due to S. aureus in more than a half of the cases, microorganism that often persists as bronchial colonized in these patients (9/10 [90%] vs. 2/7 [28.6%], p=0.034, Fisher’s exact test). In conclusion, the bronchial microbiome had significantly higher diversity than the microbial flora lodged in the oropharynx in early stage CF. Although the RA of the Staphylococcus genus was low in bronchial secretions and did not reach a dominance pattern, slight overrepresentations of this genus was associated with higher exacerbation frequencies in these patients.